Kesan penggunaan peta konsep terhadap pencapaian sains pelajar tingkatan satu - Shahril, Nordin (2016)
The phenomena of memorizing facts impacted the effectiveness of teaching and learning practises, and had caught the attention of many educational psychologists. This situation had also contributed to misconceptions in various areas in science including environmental science. This study aims to compare teachings using concept map approach based on constructivisme theory with teachings using traditional approach (OHP transparencies) on the topic of ‘Air Around Us’ in form one science subject. This study used both quantitative and qualitative approach. For the quantitative approach, the pre test and post test control group quasi-experiment research design was employed. Two classes were randomly selected from 11 classes within the research site. The sample size for the quantitative approach was 60 students whereby 30 students were in the experimental group and 30 students in the control group. Semi-structured face-to-face interviews were used to collect the qualitataive data whereby eight respondents were purposively selected, four were from the experimental group and four from the control group. The findings show that students who were exposed to concept maps performed better than students who were exposed to to traditional approach. The findings also show that students who were taught using concept maps were able to relate the concepts and shown positive perceptions towards the use of concept maps in learning the topic of ‘Air Around Us’. This study contributes to the field of science education within the context of understanding and construction of science concepts among lower secondary school students. The study also implies that there is a need for science educators in secondary schools to vary their approaches in teaching science concepts as proposed by the Ministry of Education.